2008
DOI: 10.1089/dis.2008.111715
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Pre-Dialysis Epoetin Alfa on Health Care and Work Loss Costs in Chronic Kidney Disease: An Employer's Perspective

Abstract: The objective of the study was to quantify the direct and indirect incremental costs of epoetin alpha (EPO) therapy for anemia in pre-dialysis chronic kidney disease (CKD). Using employer claims data from January 1998 to January 2005, direct (medical and pharmacy) and indirect (sick leave and disability) costs were compared between CKD-anemic patients treated with EPO before dialysis (n = 199) and those not treated with an erythropoiesis-stimulating therapy (EST) (n = 196). Among the results, incremental direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…As noted, some conditions fit across categories (eg, preexisting and advancing cardiovascular disease) and the presence of multiple risk factors and/or comorbid illnesses leads to progression of CKD and increased mortality. 19 Risk factors with overwhelming impacts on patients and health care systems include diabetes, [20][21][22][23][24][25] anemia, 20,[22][23][24][25][26][27][28][29][30][31] hypertension, [20][21][22][23]25,27,31 and hyperlipidemia. 4,20,[32][33][34][35] Patients with multiple risk factors and/or comorbidities bear the greatest burden.…”
Section: Risk Factors and Comorbid Illnessmentioning
confidence: 99%
“…As noted, some conditions fit across categories (eg, preexisting and advancing cardiovascular disease) and the presence of multiple risk factors and/or comorbid illnesses leads to progression of CKD and increased mortality. 19 Risk factors with overwhelming impacts on patients and health care systems include diabetes, [20][21][22][23][24][25] anemia, 20,[22][23][24][25][26][27][28][29][30][31] hypertension, [20][21][22][23]25,27,31 and hyperlipidemia. 4,20,[32][33][34][35] Patients with multiple risk factors and/or comorbidities bear the greatest burden.…”
Section: Risk Factors and Comorbid Illnessmentioning
confidence: 99%
“…Furthermore, CKD is more progressive in T2DM patients with anemia as one of the attributable factor contributing the CKD progress to end‐stage kidney disease . The anemic CKD patients often report poor quality of life, cognitive impairment, sleep disturbances, and ultimately impart increased economic burden . A cross‐sectional survey study conducted in EU‐5 region found CKD patients with anemia to have the lower health‐related quality of life (HRQoL) compared to patients without anemia with an impact more evident in nondialysis patients .…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective claim database analysis found CKD patients with anemia to have 38% higher overall medical expenditure than nonanemic patients . In addition, the direct and indirect cost of treatment is also higher for anemic dialysis patients compared to untreated patients . Early identification and treatment of anemia have been shown to slow the kidney disease progression, delay the renal replacement therapy, and stabilize the renal function in nondialysis CKD patients .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations